The development and validation of the Interpersonal Support in Physical Activity Consultations Observational Tool. Issue 1 (2nd January 2016) - Rouse, Peter C.; Duda, Joan L.; Ntoumanis, Nikos; Jolly, Kate; Williams, Geoffrey C.
Abstract: This study describes the development and psychometric characteristics of an observational instrument that examines four aspects of interpersonal support (or lack of) provided during physical activity (PA) promotion consultations (i.e., Autonomy Support, Involvement, Structure and Interpersonal Control), as identified by Self-determination Theory (SDT). The reliability and validity of the Interpersonal Support in Physical Activity Consultations Observational Tool (ISPACOT) were examined within an exploratory randomised control trial. Recorded consultations ( N = 42) conducted by qualified PA advisors ( N = 14) at 13 leisure centres across the West Midlands (UK) were rated. Intra-class correlation coefficients (ICC) indicated moderate to high inter-rater reliability for overall interpersonal support (0.80), and the Autonomy Support (0.74), Involvement (0.73) and Structure (0.91) dimensions, but low reliability for Interpersonal Control (0.35). The advisors, who conducted PA promotion consultations that were rated as low in their interpersonally supportive features, were perceived by their clients as being less supportive ( F (1, 10) = 5.0, p < .05). Ratings on the ISPACOT differentiated advisors who were trained in SDT principles and those who were not. Overall, the findings provided preliminary evidence for the reliability and convergent validity of the ISPACOT.